Nekateri vidiki priznavanja privilegija zoper samoobtožbo pravnim osebam - Žaucer, Martina (Pravnik, 2013)
In the article the author deals with the question of recognizing procedural safeguards arising from the privilege against self-incrimination to legal entities. The author bases her article on the nature of the privilege against self-incrimination as a principle of the criminal procedure and she initially defines its subject and scope. The author attempts to answer the question stated by analyzing professional debates which have emerged in the European legal area in the recent years and establish a position on acceptability, argumentation of the approaches. In the beginning she elaborates on the so-called subjective theory which states that the privilege is a type of legal protection against potential force for the accused, the purpose of which is to protect its personal rights. Then she moves to the analysis of the objective theory which explains the privilege against self-incrimination as a completely objective procedural principle. The author then analyses the so-called guilt theory which in German theory Friedrich Von Freier argues for, then she polemicizes with the author about the shortcomings of the guilt theory. The key question is whether human rights should be recognized to a legal entity as a so-called derivative entity. In doing so the author relies on positions of the European Court of Human Rights which has already decided on procedural safeguards arising from ambient and communicational privacy to legal entities and also analyses the Constitutional Court of the Republic of Slovenia Decision U-I-108/99-14 of 20 March 2003. The author sums up her positions in an attempt to provide an answer which would represent an alternative to the objective as well as the subjective approach and to the guilt theory.
Keywords: človekove pravice; human rights; kazenski postopek; kazniva dejanja; krivda; pravne osebe; procesno pravo